Development and characterization of a "store and create" microfluidic device to determine the heterogeneous freezing properties of ice nucleating particles. Issue 1 (2nd January 2020) - Brubaker, Thomas; Polen, Michael; Cheng, Perry; Ekambaram, Vinay; Somers, Josh; Anna, Shelley L.; Sullivan, Ryan C.
Abstract: Understanding heterogeneous ice nucleation induced by ice nucleating particles (INPs) is hindered by analytical challenges in accurately determining the freezing temperature spectrum, abundance, and physicochemical properties of INPs. Here we evaluate the performance of a microfluidic device that employs a "store and create" approach to measure the ice nucleation properties of approximately 600 uniformly sized nanoliter water droplets. These droplets are immersed in surfactant-free environmentally sustainable squalene oil and do not contact the polymer walls of the microfluidic device. The device interfaced with a cold plate temperature controller has a greatly reduced background freezing temperature spectrum for filtered water droplets compared to conventional microliter droplet-on-substrate freezing methods. Droplets containing particles of interest are readily generated on-chip from a suspension of particles in water. Background freezing for 6 nL water droplets exhibits a median freezing temperature of −33.7  ±  0.4 °C, close to the theoretical freezing temperature of −34.5 °C. The immersion freezing temperature spectra obtained from Snomax bacterial and illite mineral particles compares well with literature data, and the freezing contribution from either type of particle can be separated from a mixed suspension. Our approach generates a highly uniform droplet size distribution, causes no clogging of the microfluidic device, and is capable of reproducible droplet refreezes. The high-resolution freezing spectra obtained from large droplet number arrays enables the use of the derivative INP temperature spectrum analysis to quantitatively distinguish between different classes of INPs. The lower and consistent filtered water background freezing temperature enables measurements of almost the entire immersion freezing temperature regime from −33 to 0 °C, and quantification of weaker but often abundant INPs such as those found in biomass-burning smoke aerosol. Copyright © 2019 American Association for Aerosol Research